1986
DOI: 10.1111/j.1755-3768.1986.tb06947.x
|View full text |Cite
|
Sign up to set email alerts
|

Micropsia and metamorphopsia in the re‐attached macula following retinal detachment

Abstract: Macular dysfunction was studied in 7 patients recovering after surgery for a retinal detachment involving the macula. The degree of disturbed size perception (dysmetropsia) and metamorphopsia was measured in parallel with letter and grating acuity in patients during the recovery process for time periods up to 47 months following successful re-attachment. The demonstration of dysmetropsia, quantitatively assessed by a matching technique, in several patients indicate that the spatial density of the macular photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In another series consisting of six eyes with macula-off RRDs, all patients presented with metamorphopsia, which faded with time but persisted in four eyes (66.67%) at 5 years to 6 years after scleral buckling 6. Similarly, in a study7 that included seven eyes with macula-off RRDs, during the postoperative period all seven patients showed metamorphopsia of varying degrees. And this symptom remained in five eyes (71.43%) at 18–27 months after scleral buckling surgery.…”
Section: Discussionmentioning
confidence: 89%
“…In another series consisting of six eyes with macula-off RRDs, all patients presented with metamorphopsia, which faded with time but persisted in four eyes (66.67%) at 5 years to 6 years after scleral buckling 6. Similarly, in a study7 that included seven eyes with macula-off RRDs, during the postoperative period all seven patients showed metamorphopsia of varying degrees. And this symptom remained in five eyes (71.43%) at 18–27 months after scleral buckling surgery.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that visual acuity, metamorphopsia, and aniseikonia improve over a duration of several years in eyes with ERM, eyes with MH, and eyes with RRD. [9,[34][35][36] Other limitations of the study were its relatively small sample size and the retrospective design. Nevertheless, the present study revealed differences in postoperative visual function changes in eyes with distinct macular morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…Sjöstrand et al . investigated aniseikonia after surgery for macula-off RD and found that micropsia was present in 3 of 7 patients and transient CME could be detected in 2 of these cases 15 . We previously investigated aniseikonia and microstructure after RD surgery, and reported that 21% of eyes with micropsia exhibit CME 7 .…”
Section: Discussionmentioning
confidence: 99%